The Congo plunder and resistance - Renton, David (London Zed Books, 2007)
This book traces the story of the Congo from the unleashing of King Leopard's fury across the region in the 19th century, to the Western sponsored murder of Patrice Lumumba in 1961 to the war that has ravaged the country since 1997.
Includes bibliographical references (p. [211]-231)
Keywords: Imperialism-History.